The paleovedic diet : a complete program to burn fat, increase energy, and reverse disease - Palanisamy, Akil (Skyhorse Publishing, 2015)
In The Paleovedic Diet, Dr. Akil Palanisamy, MD, offers a comprehensive roadmap to optimal health combining the most effective aspects of the Paleo diet with Ayurveda, the time-tested traditional medical system of India, and the latest scientific research. Making complex ideas understandable and accessible, Dr. Palanisamy delivers a simple, customized diet and lifestyle program to fit your unique body type. Drawing upon on his extensive training and clinical experience, Dr. Palanisamy skillfully separates fact from fiction, providing clarity on issues such as gluten sensitivity, misconceptions about carbs, meat-eating versus vegetarianism, good and bad fats, unknown superfoods (you'll be surprised to see what's included), nutritional supplements, and the critically important gut bacteria comprising your microbiome. The Paleovedic Diet provides definitive, practical guidance on what to eat, how to move, how to sleep, how to manage stress, and even how to breathe. Palanisamy's revolutionary three-week program (with meal plan and recipes) utilizes delicious nourishing foods, powerful healing spices, and intensive detoxification techniques to help you transform your body and mind.